2002
DOI: 10.1046/j.1365-2893.2002.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

World‐wide epidemiology of HBeAg‐negative chronic hepatitis B and associated precore and core promoter variants

Abstract: Hepatitis B is a serious disease that is endemic in many parts of the world. A significant proportion of patients with chronic hepatitis B (CHB) are infected with a variant form of the hepatitis B virus (HBV) which decreases or abolishes the production of hepatitis B e-antigen (HBeAg). The purpose of this literature review is to describe the epidemiology of HBeAg-negative CHB (e-CHB) worldwide. A literature search was conducted to identify studies pertaining to e-CHB and underlying variants (precore and core p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
237
1
11

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(259 citation statements)
references
References 73 publications
10
237
1
11
Order By: Relevance
“…Meanwhile, other authors studying the prevalence of these cases observed that in the last decades there has been a gradual increase in the prevalence of HBeAg-negative CHB [6]. However, a more recent multi-center study of the world prevalence of HBeAg-negative CHB showed an increased prevalence of HBeAg-negative disease in chronic HBsAg carriers (33%) [11]. The elevated prevalence of HBeAgnegative CHB obtained in this study confirms the progressive tendency of the prevalence of HBeAg-negative CHB, possibly influenced by the type of prevalent transmission and by the high endemicity of the area studied [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, other authors studying the prevalence of these cases observed that in the last decades there has been a gradual increase in the prevalence of HBeAg-negative CHB [6]. However, a more recent multi-center study of the world prevalence of HBeAg-negative CHB showed an increased prevalence of HBeAg-negative disease in chronic HBsAg carriers (33%) [11]. The elevated prevalence of HBeAgnegative CHB obtained in this study confirms the progressive tendency of the prevalence of HBeAg-negative CHB, possibly influenced by the type of prevalent transmission and by the high endemicity of the area studied [11].…”
Section: Discussionmentioning
confidence: 99%
“…The precore mutation was detected in up to 95% of HBeAg-negative patients, but it is more prevalent in Mediterranean countries. There are few data with respect to core promoter mutations outside Asia where mean values of prevalence among HBeAg-negatives was found to be 77% [11]. Based on studies conducted in Campinas (Brazil), about 70% of HBsAg-positive patients are HBeAg negative, with elevated potential of mutations in the precore or core promoter region [45].…”
Section: Clinico-epidemiological Manifestationsmentioning
confidence: 99%
“…The other common HBV variants include double mutations in the basal core promotor (BCP) region (A1762T/ G1764A), which overlap with the ORF of the X gene and result in substantial decreases in HBeAg production [5]. These dual mutants have been reported in up to 50-80% of patients with HBeAg-negative chronic hepatitis B in Europe and Asia [6], and have been implicated in HCC development [7][8][9]. Apart from these variants, other mutations, such as T1753C/A/G in the BCP region and C1653T in the enhancer II region (EnhII) have become increasingly recognized as being associated with the outcome of chronic HBV infection, including HCC development [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…31 Importantly, HBV reactivation may occur, either as a result of HBeAg seroreversion (ie, restored HBeAg positivity caused by reactivation of wildtype HBV), or, more frequently, as a result of the emergence of HBV mutants that no longer express HBeAg (ie, precore or basal core promoter [PC/BCP] mutants); the latter event, which results in HBeAg-negative CHB, is particularly common among patients from Asia or the Mediterranean, where the prevalence of PC/BCP mutants is high. 32 HBV reactivation can occur after years or decades of the inactive carrier state and represents, especially in the case of HBeAg-negative CHB, a late stage of the infection generally associated with advanced liver disease. [21][22][23] 37 ), (2) people who were not vaccinated as infants and whose parents were born in regions with high HBV endemicity (Southeast Asia, China, sub-Saharan Africa), (3) people needing chemotherapy or immunosuppressive therapy, (4) people with multiple sexual partners or a history of sexually transmitted disease, (5) people who have ever used injecting drugs, (6) individuals infected with human immunodeficiency virus or hepatitis C virus, and (7) household contacts or sexual partners of HBV-infected people.…”
Section: Markers Of Hbv Infection and Chb Disease Progressionmentioning
confidence: 99%